Repair of Iron Centers RIC protein contributes to the virulence of Staphylococcus aureus - Silva, Liliana O. (2019)
RICs are a family of bacterial proteins involved in the repair of iron centers containing proteins damaged by the antimicrobial reactive species liberated by the innate immune system of infected hosts. Staphylococcus aureus is a human pathogen with increasing antibiotic resistance that also contains a RIC-like protein. In this work, we show that the survival of S. aureus within macrophages decreases upon inactivation of ric, and that the viability was restored to levels similar to the wild-type strain by reintroduction of ric via in trans complementation. Importantly, in macrophages that do not produce reactive oxygen species, the lower survival of the ric mutant was no longer observed. In lung epithelial cells, the intracellular viability of the S. aureus ric mutant was also shown to be lower than that of the wild-type. The wax moth larvae Galleria mellonella infected with S. aureus ric mutant presented an approximately 2.5-times higher survival when compared to the wild-type strain. Moreover, significantly lower bacterial loads were determined in the larvae hemolymph infected with strains not expressing ric, and complementation assays confirmed that this behavior was related to RIC. Furthermore, expression of the S. aureus ric gene within the larvae increased along the course of infection with a ~20-fold increase after 8 h of infection. Altogether, the data show that RIC is important for the virulence of S. aureus.